Outcomes of descending and thoracoabdominal aortic repair in connective tissue disorder patients. (31st December 2022) - Jonsson, Magnus; Blohmé, Linus; Daryapeyma, Alireza; Günther, Anders; Lundberg, Göran; Nilsson, Lena; Wahlgren, Carl-Magnus; Franco-Cereceda, Anders; Olsson, Christian
Abstract: Objectives: Open surgical repair (OSR) of descending and thoracoabdominal aortic aneurysms carries risks of mortality and major complications. Patients with connective tissue disorders (CTD) are younger and require safe, efficient treatment with long-term durability. This study provides current outcome data to help inform treatment decisions. Methods: All OSRs of descending thoracic aortic aneurysm (DTAA) or thoracoabdominal aortic aneurysm (TAAA) from January 2011 to July 2021 were included in a retrospective cohort study. Primary outcome measures were early and follow-up mortality and reintervention. Secondary outcome measures were major complications. Kaplan-Meier methods were used to estimate reintervention-free survival. Results: A total of 26 OSRs (7 DTAA, 19 TAAA) were performed in 23 patients: 20 (77%) Marfan and 6 (23%) Loeys-Dietz syndrome; median age 43 years. Aortic dissection was present in 100% and 3/26 (12%) were urgent. Early mortality was 1/26 (3.8%). No patient suffered spinal cord ischemia, stroke, vocal cord paralysis, or re-exploration for bleeding. The transient respiratory failure occurred in 19% (5/26) and transient renal replacement therapy in 15% (4/26). Renal function normalized in all patients within 3 months. During follow-up (median 4.6, range 0–11 years) there were no deaths and only one re-intervention on a previously operated aortic segment, resulting in 92% reintervention-free survival at 5 years. Conclusions: In dedicated units, open surgical DTAA and TAAA repair in patients with CTD can be performed with a very low risk of death, severe complications and, late re-intervention. For CTD patients with reasonable risk, OSR should remain the first line of treatment.